2021
DOI: 10.1038/s41598-021-94193-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the activity of transposable elements and genes involved in their silencing in the newt Cynops orientalis, a species with a giant genome

Abstract: Caudata is an order of amphibians with great variation in genome size, which can reach enormous dimensions in salamanders. In this work, we analysed the activity of transposable elements (TEs) in the transcriptomes obtained from female and male gonads of the Chinese fire-bellied newt, Cynops orientalis, a species with a genome about 12-fold larger than the human genome. We also compared these data with genomes of two basal sarcopterygians, coelacanth and lungfish. In the newt our findings highlighted a major i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…Transposable element expression is higher in R. sibiricus testes than ovaries, a pattern also reported in Drosophila (Wei et al, 2022) and the medaka fish O. latipes (Saint-Leandre et al, 2020;Dechaud et al, 2021), but opposite the pattern reported in the carrion crow Corvus corone (Warmuth et al, 2022) and different from the non-sex-biased TE expression in the newt C. orientalis (Carducci et al, 2021). In Drosophila, testes expression levels of TE-mapping piRNAs and piRNA pathway genes, as well as the ping-pong signature, are lower than ovary expression levels, suggesting that lower male piRNAmediated silencing contributes to higher male TE expression (Saint- Leandre et al, 2020;Chen et al, 2021).…”
Section: Sex-biased Te Expression and Silencingmentioning
confidence: 57%
See 1 more Smart Citation
“…Transposable element expression is higher in R. sibiricus testes than ovaries, a pattern also reported in Drosophila (Wei et al, 2022) and the medaka fish O. latipes (Saint-Leandre et al, 2020;Dechaud et al, 2021), but opposite the pattern reported in the carrion crow Corvus corone (Warmuth et al, 2022) and different from the non-sex-biased TE expression in the newt C. orientalis (Carducci et al, 2021). In Drosophila, testes expression levels of TE-mapping piRNAs and piRNA pathway genes, as well as the ping-pong signature, are lower than ovary expression levels, suggesting that lower male piRNAmediated silencing contributes to higher male TE expression (Saint- Leandre et al, 2020;Chen et al, 2021).…”
Section: Sex-biased Te Expression and Silencingmentioning
confidence: 57%
“…Transcriptomic data reveal a similarly mixed picture: for some piRNA pathway genes, germline expression is higher in salamanders (represented by the fire-bellied newt Cynops orientalis, ~44 Gb) than in the African lungfish, whereas for other genes, the pattern is reversed; comparisons with genomes of more typical size (coelacanth Latimeria menadoensis and zebrafish Danio rerio) show patterns of both higher and lower germline expression of TE silencing genes in the species with gigantic genomes (Biscotti et al, 2017;Carducci et al, 2021). Small RNA sequence data from the gonads of the northern dusky salamander Desmognathus fuscus (~15 Gb) reveal lower percentages of TE-mapping piRNAs than are found in smaller genomes, suggesting a less comprehensive TEtargeting piRNA pool in the gigantic genome (Madison-Villar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Transposable element expression is higher in R. sibiricus testes than ovaries, a pattern also reported in Drosophila (Wei et al, 2022) and Oryzias latipes (the medaka fish) (Saint-Leandre et al, 2020;Dechaud et al, 2021), but opposite the pattern reported in Corvus corone (carrion crow) (Warmuth et al, 2022) and different from the non-sex-biased TE expression in the fire-bellied newt Cynops orientalis (Carducci et al, 2021). In Drosophila, testes expression levels of TE-mapping piRNAs and piRNA pathway genes, as well as the pingpong signature, are lower than ovary expression levels, suggesting that lower male piRNAmediated silencing contributes to higher male TE expression (Saint-Leandre et al, 2020;Chen et al, 2021).…”
Section: Sex-biased Te Expression and Silencingmentioning
confidence: 64%
“…On the other hand, in the African lungfish, Wang et al (2021) suggested that the KRAB-ZFP TE transcriptional silencing machinery has expanded in scope in response to the high genomic TE load. Similarly, in the fire-bellied newt Cynops orientalis , it was suggested that TE silencing is now enhanced in response to high TE load, which accumulated in the past during a period of increased TE mobilization (Carducci et al, 2021). In both of these examples, the TEs are suggested to be currently on the defensive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation